EXPRESSIVE SPEECH ACTS IN STAND-UP COMEDY BY RADITYA DIKA - Nurpadilah, Sintia Dona; Ningsih, Rahayu; Noerbayani, Pani; Basra, Sri Meiweni (IPI Garut Press, 2024)
This study delved into the realm of expressive speech acts within stand-up comedy, with a specific focus on Raditya Dika's